The added value of SPECT/CT in the painful foot and ankle: A review of the literature. Issue 7 (October 2021) - Eelsing, Robin; Hemke, Robert; Schepers, Tim
Highlights: When Whe diagnosis on standard imaging modalities is inconclusive or when the patient has prolonged pain, SPECT/CT is useful in the painful foot and ankle. SPECT/CT makes it possible to visualize the combination of pathologic processes and morphologic changes. Despite the use of SPECT/CT in the foot and ankle seems promising, SPECT/CTS is currently not used as much as it could be for diagnosing lesions of the distal parts of the lower extremities. Abstract: Introduction: Foot and ankle injuries are common. Radiographic assessment is difficult because of the complex anatomy. In the past decade SPECT/CT made its introduction in assessing bone pathology, it combines both morphologic and pathologic imaging in one image aiming to increase sensitivity and specificity when compared with MRI or CT alone. The purpose of this review was to provide a literature overview on the diagnostic value of SPECT/CT in foot and ankle pathology. Methods: A literature search was conducted in the databases of PubMed and EMBASE between January 2004 and September 2019 for articles describing the diagnostic value of SPECT/CT in foot and ankle pathology. For assessment of methodological quality of each study included in the analysis, QUADAS-2 checklist was used. Main outcomes were change of management, improved diagnosis and symptomatic improvement. Results: A total of eight studies were identified describing the diagnostic value of SPECT/CT in foot and ankle pathology based on patient data. The combined analysis shows that change of management and improved diagnosis occurred in 48–62% and 40–79% of the patients when compared with other imaging modalities and/or clinical assessment. Symptomatic improvement due to treatment based on SPECT/CT findings occurred in 92% of the patients. Conclusion: SPECT/CT is useful when diagnosis based on other imaging modalities is inconclusive or when treatment based on these modalities does not lead to the desired symptomatic improvement.